Corporate financial reporting: history, development and future directions - Prinsloo, K S (Keith Stephen) (Rhodes University, Faculty of Commerce, Department of Accounting, 1983)
KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Corporations -- Finance; Financial statements; Accounting